The Influence of Sharia Supervisory Board Characteristics on the Maqashid Shariah Index in Islamic Commercial Banks - Setianingsih, Ratih; Mai, Muhamad Umar; Ruhana, Nafisah; Putranda, Muhammad Imaduddin; Sumiyati, Sumiyati (Journal of Applied Islamic Economics and Finance, 2025)
This study aims to analyze the effect of the characteristics of the Sharia Supervisory Board on the Maqashid Syariah Index at Islamic commercial banks in Indonesia for the period 2014-2023. This study uses a quantitative method, descriptive approach, with the sample being the entire population of this study, namely all Islamic commercial banks in Indonesia registered with the OJK during the period 2014-2023, a many of 16 Islamic commercial banks. Hypothesis testing in this study uses panel data regression analysis and Stata 17 as a tool. The results showed that age has a significant positive effect on the Maqashid Syariah Index. In contrast, size, tenure, and proportion of women have a significant negative effect on the Maqashid Syariah Index. Meanwhile, the frequency of meetings has no effect on the Maqashid Syariah Index.